2015
DOI: 10.1007/s00603-015-0784-0
|View full text |Cite
|
Sign up to set email alerts
|

Microseismic Monitoring of Strainburst Activities in Deep Tunnels at the Jinping II Hydropower Station, China

Abstract: Rockbursts were frequently encountered during the construction of deep tunnels at the Jinping II hydropower station, Southwest China. Investigations of the possibility of rockbursts during tunnel boring machine (TBM) and drilling and blasting (D&B) advancement are necessary to guide the construction of tunnels and to protect personnel and TBM equipment from strainburst-related accidents. A real-time, movable microseismic monitoring system was installed to forecast strainburst locations ahead of the tunnel face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(28 citation statements)
references
References 27 publications
(40 reference statements)
0
28
0
Order By: Relevance
“…ese two significant geohazards could affect the safety of personnel and infrastructure in excavations and deep underground mines. For example, severe strain burst occurred along a considerable length of tunnel section during tunnel excavation of the China Jinping II hydropower station project [5].…”
Section: Introductionmentioning
confidence: 99%
“…ese two significant geohazards could affect the safety of personnel and infrastructure in excavations and deep underground mines. For example, severe strain burst occurred along a considerable length of tunnel section during tunnel excavation of the China Jinping II hydropower station project [5].…”
Section: Introductionmentioning
confidence: 99%
“…e propagation directions of MS waves generated by microcracking are almost the same leading to a tangent orientation mode which was discussed by Xu et al [49]. It is clearly found that the source location errors perpendicular to the tunnel Advances in Civil Engineering 7 axis are relatively large.…”
Section: Sensor Array and Source Locationmentioning
confidence: 60%
“…Drilling and blasting are some of the most commonly used methods for rock breaking. Due to their advantages of good applicability to various geotechnical conditions, low cost, and easy operation, they have been widely applied to mine chamber excavation and water conservancy and hydropower engineering [1][2][3]. The conventional blasting technique has certain limitations and normally leads to undesirable effects.…”
Section: Introductionmentioning
confidence: 99%